The Use of Antiseptic Soap with Vaginal Discharge: Pemakaian Sabun Antiseptik Dengan Kejadian Keputihan - Nur Cholifah, Rizki Dwi; Kusumawardhani, Paramitha Amelia; Azizah, Nurul (Jurnal Kebidanan Midwiferia, 2021)
Leucorrhoea is an unusual discharge other than blood from the vagina, whether it smells or doesn't. One of the factors that influence the incidence of vaginal discharge is the use of antiseptic. Antiseptic soap which is now widely used by teenagers because of their desire to try. Because vaginal discharge sometimes adolescents choose to reduce by using an antiseptic soap. The incidence of vaginal discharge in students of the psychology faculty of the Muhammadiyah University of Sidoarjo is very high, namely 80%. The research objective was to determine the relationship between the use of antiseptic soap and the incidence of vaginal discharge. The research design used a cross sectional data approach and presented in the form of cross tabulations, then the chi square test was performed. Samples were obtained from the entire population of students in semester 2 of the psychology faculty of Muhammadiyah University as many as 30 female students. With the inclusion criteria aged 18-21 years who experienced vaginal discharge and used antiseptic soap. The data used are primary data with a questionnaire presented in the form of a frequency table, cross tabulation is carried out by the chi square test to determine the existence of a relationship. The results showed that half of female students (50.0%) used antiseptic soap well and most (66.7%) experienced physiological vaginal discharge. In conclusion, there is a relationship between the use of anisepticsoap and the incidence of vaginal discharge.